MULTIPLIKASI SEBAGAI STRATEGI NARASI FILM: Fenomena Daur Ulang dalam Industri Film Indonesia - Santyaputri, Lala Palupi (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Indonesian film industry these recent years increased rapidly and dominating Indonesian cinema. This article studied that particular of Indonesian blockbuster have known as film remakes that has been produced and made at least over twenty years and made big income for the industry. Film remakes has emerged presuppositions and prejudices. Methodology of this research used qualitative descriptive, data collecting through literature and focus group discussion. The research object has been chosen as film remakes which required more than one million spectators. Therefore of special interest to studies of film adaptation, for by exposing such syntheses, and by continually broadening how we understand cinema in relation to narrative. Narrative structure of the film remakes discovered and explored the impact of film remakes on narration multiplicity